The extreme weather risk indicators (EWRI) for the European transport system - Molarius, R.; Könönen, V.; Leviakangas, Pekka; Zulkarnain; Rönty, J.; Hietajärvi, A.; Oiva, K. (Springer Netherlands, 2014)
The European 7th Framework Programme project Extreme Weather impacts on European Networks of Transport devised a holistic analysis of extreme weather risks for the transport system. The analysis provided an overview of extreme weather risks, or a risk panorama. The risk panorama was built on a probabilistic approach to extreme weather phenomena occurrences and on vulnerability analysis based on selected macro-level economic and transport system indicators of the member states of EU-27. The panorama covers all transport modes and views infrastructure-related risks, time delay risks, and accidents risks. In addition to climatic circumstances, the devised risk indicator is also dependent on regional circumstances, such as population and transport density and income level. This paper describes the construct and application of an extreme weather risk indicator (EWRI). EWRIs are counted for each country and each transport mode separately. Furthermore, this paper also presents the most significant extreme weather events in different parts of Europe and on the transport modes they affect the most.